RELATIONS BETWEEN THE UZBEKISTAN SSR AND AFGHANISTAN (1920-1990) - Samadova Ferangiz (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article scientifically analyzes the political, economic, cultural, and military relations established between the Uzbek Soviet Socialist Republic and Afghanistan during the period of 1920–1990. The study also examines economic assistance, infrastructural projects, personnel training systems implemented through the Uzbek SSR, and the historical closeness between the two nations. In addition, the role of the Uzbek SSR as a military-logistical base during the Soviet–Afghan War of 1979–1989 is analyzed. The results of the research are of significant academic importance for a deeper understanding of the historical relations between Uzbekistan and Afghanistan, as well as the geopolitical processes in the Central Asian region.